SAPHATA DALAM BEBERAPA PRASASTI - Rita Istari (Berkala Arkeologi, 2007)
In writing the ancient history of Indonesia, it is necessary not only historical sources in the form of relics of the past / artifacts, but also in the form of written sources, one of which is inscriptions. In archaeological understanding, the inscription is the official royal charter carved in stone or metal pot, usually containing decisions regarding the designation of an area to be a sima / perdikan area. The determination of an area to be sima by a king or family is usually done if the area is considered meritorious and for the benefit of a sacred building. However, there are also inscriptions containing court decisions and laws. Apart from stone and metal, ancient writing can also be written on lontar, pottery, statues, and possibly other perishable objects such as bamboo and wood, so they are no longer found today.